1996
DOI: 10.1046/j.1469-0705.1996.08020087.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow velocity waveforms from peripheral pulmonary arteries in normally grown and growth‐retarded fetuses

Abstract: The objective of this study was to describe blood flow velocity waveforms of fetal peripheral pulmonary arteries in normally grown and growth-retarded fetuses. Doppler studies were performed in 182 normally grown fetuses (gestational age 18-40 weeks) and in 61 growth-retarded fetuses (gestational age 24-36 weeks) that were free from structural and chromosomal abnormalities and whose umbilical and middle cerebral artery Doppler findings suggested uteroplacental insufficiency as the most likely etiology of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 0 publications
6
40
2
4
Order By: Relevance
“…Although experimental data 15,16 and some studies in humans 17 suggest that the normal dominance of the right ventricle is cancelled during challenge, our study supports that in fetuses with increased pulsatility of the umbilical artery the right ventricle actually takes an increased proportion of the load 18,19 . This is in keeping with other mechanisms seen in such fetuses: reduced size of and shunting through the foramen ovale 7,20 , increased resistance in the pulmonary circuit 21 , with correspondingly less venous return to the left heart, and retrograde blood flow at the aortic isthmus 7,22 to further supply the aortic arch and carotid arteries with right ventricular blood via the ductus arteriosus. A shift to the left of the watershed area between portal and umbilical venous supply to the liver 23,24 and an augmented blood velocity in the hepatic artery 25 will change the fetal circulation in the same direction.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although experimental data 15,16 and some studies in humans 17 suggest that the normal dominance of the right ventricle is cancelled during challenge, our study supports that in fetuses with increased pulsatility of the umbilical artery the right ventricle actually takes an increased proportion of the load 18,19 . This is in keeping with other mechanisms seen in such fetuses: reduced size of and shunting through the foramen ovale 7,20 , increased resistance in the pulmonary circuit 21 , with correspondingly less venous return to the left heart, and retrograde blood flow at the aortic isthmus 7,22 to further supply the aortic arch and carotid arteries with right ventricular blood via the ductus arteriosus. A shift to the left of the watershed area between portal and umbilical venous supply to the liver 23,24 and an augmented blood velocity in the hepatic artery 25 will change the fetal circulation in the same direction.…”
Section: Discussionsupporting
confidence: 82%
“…• in 56 recordings and the median was 16 (IQR, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] • in the remaining 141. The fetoplacental blood flow was calculated as π · (D/2) 2 · V wmean , and its fraction of the CCO was calculated as a percentage.…”
Section: Sonographymentioning
confidence: 99%
“…With the advent of color Doppler, tiny vessels became visible and thus reliably accessible to spectral Doppler evaluation. Reports emerged on pulmonary arterial and venous flow, on measurements across the fetal shunts such as the ductus arteriosus and foramen ovale, and even on the coronary artery and venous systems 37,[41][42][43][44][45][46][47][48][49][50] . The quantification of tricuspid valve insufficiency was shown to reveal valuable information on etiology and prognosis [51][52][53][54] .…”
Section: Spectral Dopplermentioning
confidence: 99%
“…It was shown that in the normal human fetus the percentage of cardiac output perfusing the lung reaches 20% and is thus much higher than the rate of 5-7% known from animal experiments 89 . Pulmonary Doppler was then performed in fetuses at high risk for lung hypoplasia 90,91 , under hypoxia 48 and hyperoxygenation 92 as well as in heart defects 93 . We think that this new field of investigation has great potential and should be developed in the future, especially because lung diseases are the leading cause of death in the neonatal period.…”
Section: Fetal Echocardiography and The Lungmentioning
confidence: 99%
“…10,11 Only sparse data are available on the inverse relationship between Po 2 and downstream impedance in the peripheral pulmonary arteries, established in growth-restricted human fetuses. 12 It has been shown in postmortem studies that pulmonary hypoplasia is associated with underdevelopment and structural changes of the pulmonary vascular bed. A decrease in the total size of the pulmonary vascular bed, a decrease in the number of vessels per unit of lung tissue, and an increase of pulmonary arterial smooth muscle thickness have been described.…”
mentioning
confidence: 99%